2012
DOI: 10.1136/annrheumdis-2011-200690
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial diseases and antitumour necrosis factor therapy in USA

Abstract: Among anti-TNF users in USA, mycobacterial disease rates are elevated, and NTM is associated with RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
175
1
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(192 citation statements)
references
References 27 publications
8
175
1
8
Order By: Relevance
“…This may be explained by recent epidemiological studies [23,26] showing that NTM lung disease is most likely to develop in middle/old aged patients and in immunocompetent subjects. WINTHROP et al [27] revealed that NTM disease was associated rheumatoid arthritis among patients treated with a TNF-a antagonist. Among the six patients with NTM lung disease that developed during anti-TNF-a therapy, one had ulcerative colitis and five had rheumatoid arthritis; all six patients were middle-to-old age (age range 42-72 years).…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by recent epidemiological studies [23,26] showing that NTM lung disease is most likely to develop in middle/old aged patients and in immunocompetent subjects. WINTHROP et al [27] revealed that NTM disease was associated rheumatoid arthritis among patients treated with a TNF-a antagonist. Among the six patients with NTM lung disease that developed during anti-TNF-a therapy, one had ulcerative colitis and five had rheumatoid arthritis; all six patients were middle-to-old age (age range 42-72 years).…”
Section: Discussionmentioning
confidence: 99%
“…Les bacilles qui ne sont pas éliminés par ces premières défenses se multiplient à l'intérieur des cellules dendritiques. Ils sont conduits aux ganglions régionaux où leurs antigènes sont présentés aux lymphocytes CD 4 + et CD 8 + qui vont être activés. C'est la deuxième étape dite adaptative.…”
Section: Histoire Naturelle De La Tuberculoseunclassified
“…Il était encore 2 à 4 fois plus important sous anti-TNFα. Au cours de la maladie de Crohn, le risque semble similaire même si l'incidence de TB chez les malades sans anti-TNFα n'a pas été étudiée [6][7][8].…”
Section: Les Agents Anti-tnfαunclassified
See 1 more Smart Citation
“…Especially in female patients, D6S0009i MICA polymorphism (MICA-TM), and particularly its A6 allele, has been found in the above study has conferring genetic susceptibility to MAC. Also, since TNF locus, located in class III MHC region, is an important multifunctional proinflammatory agent, some therapies, especially in autoimmune diseases such as rheumatoid arthritis, uses TNF inhibitors which have been associated to an increased risk for MAC and other non-tuberculosis mycobacteriosis, besides TB mentioned above [105] . Despite with inconclusive results, other studies suggest that specific HLA alleles could be associated with the development of pulmonary MAC infection.…”
Section: Pulmonary Mac Infectionmentioning
confidence: 99%